Therapeutic Adherence in Patients with Diabetes Mellitus Non-insulin Dependent - Andree Cevallos Mera, Carlos; Mabel Sanchez Rodriguez, Johanna; Mariuxi Sanchez Zambrano, Kimberly; Mirella Cedeño Holguin, Dolores (International Journal of Psychosocial Rehabilitation, 2020)
The research arises from the empirical appreciation that there is insufficient therapeutic adherence by patients with non-insulin-dependent diabetes mellitus in the geographic area studied. Diabetes is considered a chronic, progressive, and incurable disease, where the diagnosed individual is at risk of developing chronic complications at some point. The objective is to determine factors that intervene in the deficiency of therapeutic adherence in people with non-insulin-dependent diabetes mellitus and its repercussions on health. For the development of the investigation, the inductive-deductive method and the analysis-synthesis method were executed. It was determined that the greatest health determinant in the population of patients with non-insulin-dependent diabetes mellitus is the acquisition of healthy habits. They tend to omit failure to comply with treatment. The main reason for this is not to harm the doctor-patient relationship. Likewise, they minimize the level of adherence to healthy lifestyles. However, when pricing overweight, obesity, or complementary test results, a different picture is reflected than that expressed in the consultation.